Development and Validation of the Particle into Nitroxide Quencher System with BPEAnit Probe for High-Sensitivity Reactive Oxygen Species Detection in Atmospheric Monitoring - Ruiwen Wang; Jiawen Li; Hao Wang; Shuo Deng; Congrong He; Branka Miljevic; Zoran Ristovski; Boguang Wang (Sensors)
Reactive oxygen species (ROS) play an important role in atmospheric pollution, and their detection is essential for assessing air quality and health risks. This study developed and validated a standardized methodology for using the BPEAnit probe in a specially designed particle-into-liquid sampler, the Particle Into Nitroxide Quencher (PINQ), to measure reactive oxygen species in atmospheric monitoring applications. The method demonstrated high sensitivity, with a detection limit of 0.03 nmol·m−3, robust linearity (R2 = 0.9999), and negligible system residue, ensuring accurate ROS quantification. Comparative analyses of startup conditions revealed superior baseline stability under cold start conditions despite the longer stabilization time required. The auto-oxidation of the BPEAnit probe, measured at a rate of 3.01 nmol·m−3 per hour, was identified as a critical factor for long-term monitoring, highlighting the necessity of standardized procedures to mitigate the drift effect. The study established the system’s suitability for urban air quality assessments and public health risk evaluations, offering insights into its limitations and operational challenges. Future advancements could focus on enhancing probe stability and expanding the method’s utility in diverse operational environments, thereby broadening its applicability to diverse monitoring scenarios.